Analysis of the Effect of Compensation and Employment Conflict on Employee Performance PT. Palmindo Persada - Anggela Anggela; Triana Melinda Sinaga (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of compensation and conflict on the performance of employees of PT. Palmindo Persada. This type of research is explanatory research. The population in this study were all employees who worked at PT. Palmindo Persada as many as 58 employees. The sampling technique uses a saturated sample where the entire population will be used as a research sample. In this study, the questionnaire will be distributed as measured by a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous and partial tests. The results showed that compensation and conflict partially or simultaneously had a positive and significant effect on the performance of PT. Palmindo Persada. Based on the results of this study, the implication for management is to further increase compensation and conflict.